Completeness Basic Infants Immunization To Achieve Universal Child Immunization At The Public Health Center Semparuk Sambas West Kalimantan In 2021 - Dewanti Dewanti; Soekidjo Notoatmodjo; Santi Agustina (Journal of Ageing And Family, 2022)
Completeness of immunization is something that is already complete, while is an effort to provide immunity to infants and children by incorporating BCG, Hepatitis, Polio, DPT, Measles vaccines into the body so that the body makes antibodies to prevent disease. The factors of completeness of immunization are knowledge, attitudes, availability of facilities and infrastructure, affordablity of distance, the role of posyandu cadres, the role of health workers and the role of the husband. The purpose of this study was to determine the factors that most influence the completeness of basic immunization for infants at the Semparuk Sambas public health center. This research is quantitative with a cross sectional approach. The population in this study were all mothers who had babies age 9-12 months as many as 129 mothers. Sampling technique by means of total sampling. Analyze using multiple logistic regression test using SPSS 16.0. The results of the study that the completeness of immunization in infants was 69%. The results of logistic regression showed that there was a ralitonship between education, work, attitudes, the role of posyandu cadres, the role of health workers and the role of the husband. Attitude is the most dominant variabel with an OR 3,444. Its hoped that the more positive the mother attitude will tend to pay attention to the schedule of giving immunization to her baby, the positive mother attitude will be better in giving the perception of something she knows.Keyword: immunization equipment, attitude, the role of health workers